Diversity of endophytic bacterial and fungal microbiota associated with the medicinal lichen Usnea longissima at high altitudes - Wang, Qi; Li, Jun; Yang, Jie; Zou, Yue; Zhao, Xin-Qing (Frontiers in Microbiology, 2022)
Endophytic microbial communities of lichen are emerging as novel microbial resources and for exploration of potential biotechnological applications. Here, we focused on a medicinal lichen Usnea longissima, and investigated its bacterial and fungal endophytes. Using PacBio 16S rRNA and ITS amplicon sequencing, we explored the diversity and composition of endophytic bacteria and fungi in U. longissima collected from Tibet at five altitudes ranging from 2,989 to 4,048 m. A total of 6 phyla, 12 classes, 44 genera, and 13 species of the bacterial community have been identified in U. longissima. Most members belong to Alphaproteobacteria (42.59%), Betaproteobacteria (33.84%), Clostridia (13.59%), Acidobacteria (7%), and Bacilli (1.69%). As for the fungal community, excluding the obligate fungus sequences, we identified 2 phyla, 15 classes, 65 genera, and 19 species. Lichen-related fungi of U. longissima mainly came from Ascomycota (95%), Basidiomycota (2.69%), and unidentified phyla (2.5%). The presence of the sequences that have not been characterized before suggests the novelty of the microbiota. Of particular interest is the detection of sequences related to lactic acid bacteria and budding yeast. In addition, the possible existence of harmful bacteria was also discussed. To our best knowledge, this is the first relatively detailed study on the endophytic microbiota associated with U. longissima. The results here provide the basis for further exploration of the microbial diversity in lichen and promote biotechnological applications of lichen-associated microbial strains.